Konsep Uslub Amr Bagi Konteks Akidah dalam Surah Al-Mulk Berdasarkan Pendapat Al-Awsi: The Concept of Uslub Amr in the Context of Islamic Creed in Surah Al-Mulk Based on Al-Awsi’s Opinion - Rifa’in @ Mohd Rifain, Syakirah; Pa, Mat Taib; Hussin, Mohamad; Abd. Latif, Faizuri (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
Al-Qur’an has its own beauty secret with various uses of uslub amr. This study aims to identify the implicit or secret meaning of the use of fi‘il amr in the field related to Islamic Creed. This study is a qualitative study that uses al-Awsi’s opinion and text analysis techniques based on the context of the verse by using related interpretations from past and modern scholars. Overall it is found that the use of amr for the context of Islamic Creed in surah al-Mulk is not used in any other form except fi‘il amr only. The study found that there are ten verses that use fi‘il amr for the context of Islamic Creed in surah al-Mulk. The study summarizes that fi‘il amr is used as a very firm and strong instruction on basic matters in the context of faith for matters of al-Ilahiyyat and al-Sam’iyyat because it involves faith in Allah, Angels, the Qur’an, the Messenger and the Day of Judgment which is obligatory believed by Muslims. The uslub amr used in the Qur’an has its own secrets and techniques because it has an implicit meaning for each form of amr. Therefore, the use of amr is planned and not without a specific arrangement. This needs to be learned so that it can be used as a guide and lesson in everyday life.